Detection of three Allexivirus species infecting garlic in Brazil - Melo Filho, Péricles de Albuquerque (2004)
Garlic viruses often occur in mixed infections under field conditions. In this study, garlic samples collected in three geographical areas of Brazil were tested by Dot-ELISA for the detection of allexiviruses using monoclonal specific antibodies to detect Garlic virus A (GarV-A), Garlic virus B (GarV-B), Garlic virus C (GarV-C) and a polyclonal antiserum able to detect the three virus species mentioned plus Garlic virus D (GarV-D). The detected viruses were biologically isolated by successive passages through Chenopodium quinoa. Reverse Transcriptase Polimerase Chain Reaction (RT-PCR) was performed using primers designed from specific regions of the coat protein genes of Japanese allexiviruses available in the Genetic Bank of National Center of Biotechnology Information (NCBI). By these procedures, individual garlic virus genomes were isolated and sequenced. The nucleotide and amino acid sequence analysis and the one with serological data revealed the presence of three distinct allexiviruses GarV-C, GarV-D and a recently described allexivirus, named Garlic mite-borne filamentous virus (GarMbFV), in Brazil.